2012
DOI: 10.1039/c2mt00163b
|View full text |Cite
|
Sign up to set email alerts
|

Human urinary excretion and metabolism of 82Se-enriched selenite and selenate determined by LC-ICP-MS

Abstract: Urinary excretion of selenium after ingestion of isotope labeled selenite and selenate was studied in seven healthy volunteers, 4 men and 3 women (age 28-50 years). An aqueous solution containing 330 μL (82)Se-selenate (corresponding to 74.3 μg (82)Se) was given orally and urine samples were subsequently collected during the following 24 hours. The scheme was repeated four weeks later with a 280 μL (82)Se-selenite solution (corresponding to 74.4 μg (82)Se). The amount of total Se in the urine samples was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
3
15
1
Order By: Relevance
“…Another conformity with the study of Gammelgaard et al (2012) was the particular case of one subject showing a clear increased elimination of SeSug1 with a maximum 6 h after ingestion like the subject of subgroup III in the present study. Due to the fact that Gammelgaard et al (2012) used isotope-labeled selenate, they proved the conversion of selenate to SeSug1.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Another conformity with the study of Gammelgaard et al (2012) was the particular case of one subject showing a clear increased elimination of SeSug1 with a maximum 6 h after ingestion like the subject of subgroup III in the present study. Due to the fact that Gammelgaard et al (2012) used isotope-labeled selenate, they proved the conversion of selenate to SeSug1.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with the observation of lower amounts of total selenium eliminated by TMSe eliminators, the investigation of Gammelgaard et al (2012) showed also one subject with a distinct lower elimination of 82 Se. The TMSe status was unfortunately not tested in their study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…methyl-2-acetamido-2-desoxy-1-seleno-β-d-glucopyranoside (SeSug2) and methyl-2-amino-2-desoxy-1-seleno-β-d-galactopyranoside (SeSug3) have been detected in human urine, from which SeSug1 is the most important one Gammelgaard and Bendahl 2004;Gammelgaard et al 2003Gammelgaard et al , 2005Gammelgaard et al , 2012Kuehnelt et al 2005). Another pathway is the elimination after methylation in the form of dimethylselenide via breath (Kremer et al 2005) or trimethylselenium ion via urine (Gammelgaard et al 2000;Kuehnelt et al 2006;Lu et al 2012;Marchante-Gayón et al 2001).…”
Section: Introductionmentioning
confidence: 99%